Correlation between the availability of dopamine transporter and olfactory function in healthy subjects - Pak, Kyoungjune; Kim, Keunyoung; Lee, Myung Jun; Lee, Jae Meen; Kim, Bum Soo; Kim, Seong-Jang; Kim, In Joo (European radiology, 2018)
Objectives Olfactory dysfunction in Parkinson’s disease is usually prodromal to other symptoms. In this study, we aimed to explore the association of olfactory function with the availabilities of striatal dopamine transporter (DAT) in healthy subjects. Methods Data used in the preparation of this article were obtained from Parkinson’s Progression Markers Initiative database ( www.ppmi-info.org/data ). The study population consisted of healthy controls with screening 123 I-FP-CIT single photon emission tomography (SPECT). University of Pennsylvania Smell Identification Test (UPSIT) was assessed to evaluate the olfactory function. Results: Totally, 181 healthy subjects (117 male, 64 female) with 123 I-FP-CIT SPECT data were included in this study. Specific binding ratios (SBRs) of the caudate nucleus (rho = -0.4217, p < 0.0001), putamen (rho = -0.2292, p = 0.0019), and striatum (rho=-0.3425, p < 0.0001) showed a reduction with ageing. SBRs of the caudate nucleus, putamen, and striatum were positively correlated with UPSIT (rho = 0.3716, p < 0.0001; rho = 0.3655, p < 0.0001; rho = 0.3880, p < 0.0001). After controlling for age by partial correlation, SBRs of the caudate nucleus, putamen, and striatum showed an influence on UPSIT (rho = 0.3288, p < 0.0001; rho = 0.3374, p < 0.0001; rho = 0.3511, p < 0.0001). Conclusion Olfactory function is associated with the availability of striatal DAT independent of age in healthy subjects. Key Points • Olfactory dysfunction in Parkinson’s disease is prodromal to other symptoms . • The availability of dopamine transporter showed a reduction with ageing . • Olfactory function is associated with the availability of dopamine transporter .